Student's Role in Obeying School Conditions At Mts Ar-Ridho Tanjung Mulia, Kampung Rakyat District, Labuhan Batu Selatan Regency - Sinaga, Rahmadoniati; Anjar, Agus (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to find out the role of students in obeying the rules at Mts Ar-Ridho Tanjung Mulia school. The focus of the research is student discipline. The study used a qualitative descriptive approach with the key informants being 3 teachers and a sample of 77 students. This research was carried out at the Mts Ar-Ridho Tanjung Mulia school, Kampung Rakyat Labuhanbatu Selatan district. The instrument in this study was to collect data with the methods of observation, interviews, and questionnaires. The study used techniques to analyze data, namely data reduction techniques, data presentation, and drawing conclusions. The results of the research Violations committed by students are given with sanctions that are imposed and listed in the school rules, Rules are important as a form of learning discipline because they are a guide for students to behave properly. It can be concluded that there are still some students of Mtr Ar-Ridho Tanjung Mulia Kampung Rakyat who do not obey the school rules and regulations.